Sectoral Diversification and Financing Risks in Indonesian Islamic Banks - Widarjono, Agus; Afandi, Akhsyim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
The stability of Islamic banking is crucial for financial sustainability, and sectoral diversification plays a key role in mitigating financing risks. In Indonesia, Islamic banks operate under two models: Islamic bank windows and full-fledged Islamic commercial banks, each facing unique risk exposures. This study investigates the impact of sectoral diversification across various economic sectors on the financing risks of Indonesian Islamic banks. It also examines the role of key bank-specific and macroeconomic factors, including asset size, financing volume, operational efficiency, inflation, and the COVID-19 pandemic. Using aggregate monthly data from Islamic bank windows and Islamic commercial banks spanning January 2015 to December 2023, this study employs the Autoregressive Distributed Lag (ARDL) model to assess both short-term and long-term effects on financing risks. The results indicate that concentrated sectoral financing significantly increases financing defaults for both Islamic bank windows and Islamic commercial banks. Furthermore, while larger bank size and greater operational efficiency contribute to lower financing defaults, an increase in financing volume is associated with higher risks. Inflation and the COVID-19 pandemic further exacerbate financing defaults, particularly for Islamic bank windows. These findings underscore the importance of diversifying sectoral financing to mitigate risk. Policymakers and banking practitioners should promote balanced financing strategies complemented by stringent financing monitoring to reduce default risks and enhance financial resilience.======================================================================================================== ABSTRAK - Diversifikasi Sektoral dan Risiko Pembiayaan pada Bank Syariah di Indonesia. Stabilitas perbankan syariah sangat penting bagi keberlanjutan sektor keuangan, dan diversifikasi sektor ekonomi memainkan peran kunci dalam mengurangi risiko pembiayaan. Di Indonesia, bank syariah beroperasi dalam dua model: unit usaha syariah (Islamic bank windows) dan bank umum syariah (Islamic commercial banks), yang masing-masing menghadapi eksposur risiko yang berbeda. Penelitian ini mengkaji dampak diversifikasi sektor ekonomi terhadap risiko pembiayaan bank syariah di Indonesia. Selain itu, studi ini mengeksplorasi pengaruh variabel spesifik bank dan kondisi makroekonomi, termasuk ukuran aset, volume pembiayaan, efisiensi operasional, inflasi, serta pandemi COVID-19. Data penelitian berasal dari laporan bulanan dari Unit Usaha Syariah (UUS) dan Bank Umum Syariah (BUS) dari Januari 2015 hingga Desember 2023. Analisis data dilakukan dengan model Autoregressive Distributed Lag (ARDL) yang cocok untuk menguji efek jangka pendek dan panjang dari risiko pembiayaan. Hasil penelitian menunjukkan bahwa pembiayaan yang terfokus pada sektor tertentu secara signifikan meningkatkan risiko gagal bayar pada Islamic bank windows maupun Islamic commercial banks. Selain itu, ukuran bank yang lebih besar dan efisiensi operasional yang lebih tinggi terbukti mengurangi risiko gagal bayar, namun peningkatan volume pembiayaan justru meningkatkan risiko. Inflasi dan pandemi COVID-19 semakin memperburuk risiko gagal bayar, terutama bagi UUS. Temuan ini menegaskan pentingnya diversifikasi sektor pembiayaan untuk mengurangi risiko. Para pemangku kebijakan dan praktisi perbankan disarankan untuk mendorong strategi pembiayaan yang lebih seimbang, didukung oleh pemantauan pembiayaan yang ketat guna mengurangi risiko gagal bayar serta meningkatkan ketahanan keuangan.